Yoghurt as a starter in sourdough fermentation to improve the technological and functional properties of sourdough-wheat bread - Graça, Carla (2021)
The incorporation of yoghurt as a starter in sourdough wheat bread, to improve technological and nutritional properties, was investigated. Two bread dough matrices were considered: endosperm wheat flour and blended with whole-grain flour. Two fermentation’s types were performed, two-stage sourdough bread and yeast bread fermentation. Compared with yeast dough, yoghurt-sourdough fermentation promoted considerable changes in chemical composition, particularly when whole-grain flour was conjoined with wheat flour: higher protein proteolysis degree, increase of peptide and free amino nitrogen content, solubilization of phenolic compounds (46–53%), increase of DPPH radical scavenging (54–65%) and ferric-reducing power (85–88%), were observed. As a baking ingredient, yoghurt-sourdough improved the bread crumb softness (15–12%) and delayed the staling (40–35%). Nutritionally, the glycemic index was reduced (18–32%) while protein digestibility (6–12%) and free amino acids bioavailability (50–100%) were enhanced. The addition of yoghurt and sourdough fermentation techniques offered a promising tool to improve wheat bread’s technological and functional properties